Mechanical and Electric Control of Photonic Modes in Random Dielectrics. Issue 12 (4th February 2019) - Balestri, Dario; Petruzzella, Maurangelo; Checcucci, Simona; Intonti, Francesca; Caselli, Niccolò; Sgrignuoli, Fabrizio; van Otten, Frank W. M.; Fiore, Andrea; Gurioli, Massimo
Abstract: Random dielectrics defines a class of non‐absorbing materials where the index of refraction is randomly arranged in space. Whenever the transport mean free path is sufficiently small, light can be confined in modes with very small volume. Random photonic modes have been investigated for their basic physical insights, such as Anderson localization, and recently several applications have been envisioned in the field of renewable energies, telecommunications, and quantum electrodynamics. An advantage for optoelectronics and quantum source integration offered by random systems is their high density of photonic modes, which span a large range of spectral resonances and spatial distributions, thus increasing the probability to match randomly distributed emitters. Conversely, the main disadvantage is the lack of deterministic engineering of one or more of the many random photonic modes achieved. This issue is solved by demonstrating the capability to electrically and mechanically control the random modes at telecom wavelengths in a 2D double membrane system. Very large and reversible mode tuning (up to 50 nm), both toward shorter or longer wavelength, is obtained for random modes with modal volumes of the order of few tens of (λ/ n ) 3 . Abstract : A disordered dielectric device with embedded quantum dots, which allows a fine, reversible, and large tuning of small‐volume localized random modes with mechanical and electric techniques, is presented. Mode control is illustrated with numerical simulations and experimentally observed with near‐field and standard microscopy methods. The large spectral tuning with mode steadiness makes such devices suitable for optoelectronics and quantum cavity electrodynamics applications.